A retrospective comparative study between laparoscopic and open appendectomy in teaching hospital of India - Singh, Lal Mani; Wadiwa, Yogendra Singh (International Surgery Journal, 2018)
Background: This study was aimed to compare laparoscopic with open appendicectomy and ascertain the therapeutic benefit, in the overall management of appendicitis. Laparoscopic appendicectomy though widely practiced has not gained universal approval. Laparoscopic appendicectomy in India is relatively new and the literature is exiguous. Methods: The study group consisted of 100 patients suffering from appendicitis. 40 patients underwent laparoscopic appendicectomy (LA) and 60 patients underwent open appendecectomy (OA). Comparison was based on length of hospital stay, operating time, postoperative morbidity, postoperative complications, duration of convalescence and operative cost in terms of their medians. Results: The rate of infections and overall complications (LA: 5%, OA: 11.66% were significantly lower in patients undergoing LA. The median length of stay was significantly shorter after LA (45% discharged 2nd day) than after OA (36% discharged on 4th day). VAS WAS 0-2 IN 60% cases LA and9-10 in 00% cases as compared to OA VAS Was 0-2 in15% and 9-10 in 3.33% cases. Conclusions: LA is associated with increased clinical comfort in terms of fewer wound infections, faster recovery, earlier return to work and improved cosmesis. Hospital stay for LA is significantly shorter and the one-time operative charges appear to be almost the same.